IMPLEMENTASI DIGITAL PAYMENT DI LINGKUNGAN UNIVERSITAS LABUHANBATU DAN DAMPAKNYA PADA KEPUTUSAN PENGGUNA - Nurriski Maysari; Pristiyono Pristiyono; Mesia Fitri Nasution (Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this research is to be able to provide relevant information to stakeholders related to digital payments. The research design prioritizes collaborative descriptive research with a quantitative approach with primary data collection techniques as the main research data which contains various questions in a questionnaire arranged in a Google form that is distributed to all active students within the Labuhanbatu University campus, with as many as 150 samples. Data analysis techniques in solving problems with the Smart PLS v.4.0 application to predict the model tested in the study. Based on the results of the research hypothesis test, among others, that the consumer motivation variable has not succeeded in becoming one of the factors that determine the occurrence of digital payment user decisions within the Labuhanbatu University academic community, the consumer perception variable becomes the second hypothesis which does not significantly affect digital payment user decisions within the University academic community. Labuhanbatu. This means that of the entire hypothesis, only the third hypothesis, namely the consumer behavior variable, has a strong and significant influence on digital payment user decisions in the academic community at Labuhanbatu University